ANALISIS AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI EVALUASI KINERJA MANAJEMEN TERHADAP KLAIM BPJS DI RUMAH SAKIT PANCARAN KASIH MANADO - Sumual, Jerikho Reagan; Alexander, Stanly W.; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
Accounting accountability is an accounting system that recognizes the existence of responsibility centers in a company. Accounting information on accountability is urgently needed control in management as a means for communication, motivation and assessment. The purpose of this study is to know the effectiveness accountability as a means of evaluation of management performance against BPJS claims in Hospital Pancaran Kasih Manado. Type of research conducted in this study is qualitative research. From the results of research at Hospital Pancaran Kasih Manado shows that accounting as an evaluation of management performance in service claims BPJS has been effective by referring to the National Standard Accreditation HospitalKeywords: Accounting Accountability, Management Performance